2000
DOI: 10.1139/cjpp-78-10-757
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the regulation of calcium metabolism and bone calcium content during growth in the absence of endogenous prolactin and during hyperprolactinemia: A longitudinal study in male and female Wistar rats

Abstract: Since endogenous prolactin has been shown to enhance food consumption, calcium absorption, and bone calcium turnover in the pregnant rat, the role of endogenous prolactin in the regulation of calcium metabolism was investigated in 3-day balance studies of female Wistar rats from the age of 3 to 11 weeks. The study was divided into two parts. In part I, calcium metabolism in males and females was compared. In part II, 3-week old female rats were divided into 5 groups: (i) control animals receiving 0.9% NaCl; (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Visual examination of the well-vascularized hypophyseal graft and immunohistochemical staining for PRL production were performed at the end of the experiments to confirm successful AP transplantation (10). At 4 wk after transplantation, plasma PRL levels are known to increase to 90 -100 ng/ml (28). Surgery and tissue collection.…”
Section: Methodsmentioning
confidence: 99%
“…Visual examination of the well-vascularized hypophyseal graft and immunohistochemical staining for PRL production were performed at the end of the experiments to confirm successful AP transplantation (10). At 4 wk after transplantation, plasma PRL levels are known to increase to 90 -100 ng/ml (28). Surgery and tissue collection.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the estrogen-dependent action, the effect of PRL on bone was also dependent on the circulating levels of PRL and duration of exposure [6,16]. We previously showed that the basal levels of PRL of ~7-10 ng/ml were necessary for the maintenance of the normal rate of bone turnover in nonmated adult female rats [6].…”
Section: Discussionmentioning
confidence: 99%
“…1). This technique has also been known to raise plasma PRL to 90-100 ng/ml (comparable to the levels during pregnancy) [16] and to suppress plasma estrogen below 50 pg/ml [17].…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations